Youth and the Reinvention of Politics. New Forms of Participation in the Age of Individualization and Presentification - Alteri, Luca; Leccardi, Carmen; Raffini, Luca (PARTECIPAZIONE E CONFLITTO, 2017)
According to mainstream theory, citizens and among them young people in particular are disenchanted and increasingly skeptical of representative democracy and traditional political organization. Indeed, the decline in conventional participation is accompanied by a process of the reinvention of politics, characterized by the spread of unconventional participation and innovative approaches and repertoires of action. New practices configure themselves as informal, non-institutionalized, horizontal, increasingly di-vorced from traditional collective social cleavages, but personally meaningful and individually oriented. Finally, politics also divorced from long terms projects, as the future folds back into the present, it is ab-sorbed within it and it is consumed before it can really be conceived. The present appears as the only di-mension available for the definition of choices, a fully-fledged existential horizon which includes and sub-stitutes the future and the past. The acceleration of social life and its various times renders these two di-mensions ever more evanescent as reference points for political action. Yet despite all of this, individuali-zation and presentification do not equate with depoliticization. In a con-text shaped by the privatization of social and political experience and by a presentification of life-projects, the new forms of mobilization protagonized by youth can be analyzed as the search for a collective project by means of articulating and integrating diversity – as well as a way to express a deep form of indignation. In this monographic issue of Partecipazione e Conflitto we have recollected contribution which analyze the reinvention of participation – in direction of an alter-activism - in the age of individualization and presentification,.